Enhancing attachment-based aspects of PCIT for young children with a history of maltreatment - Belanger, Kristine; Gennis, Hannah; Ottenbreit, Nicole; Racine, Nicole (Frontiers in Psychology, 2023)
Disruptive behavior difficulties, such as aggression, non-compliance, and emotional outbursts, are common among children exposed to maltreatment. Parent-Child Interaction Therapy (PCIT) is an effective parenting intervention for addressing child behavior difficulties, however, treatment retention and engagement among parents remain a concern in the clinical setting. This paper describes how the delivery of an intervention that teaches attachment theory concepts (Circle of Security -Parenting, COS-P) prior to PCIT can increase engagement and retention among parents of maltreated children and inform new coaching practices. A detailed description of how to extend and integrate COS-P concepts with PCIT for maltreated families using specific strategies is provided. Recommendations, limitations, and next steps for research are presented.